ESSENTIAL CHANGES OF THE FAMILY INSTITUTE UNDER MODERN CONDITIONS - Kolesov, V. I.; Smolonskaya, A.N. ,; Smolenskiy, S. I.; Slanov, V. P.; Fedorova, E. N. FedorovaE. N.; Moskalenko, M. S.; Timokhina, Y. Y. (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the essential features of the family paradigm in modern conditions and it establishes the causal dependencies of changes in modern society that occur with the respect to the given social institution at the ontological level. There is the analysis of the situation and prospects for the development of the family as a cultural social education which is undergoing changes. The importance of the family in the life of a person and society is established. The subject of the study is the content, factors, and ways of functioning of the family in modern Russian reality. The article compares the interdependence of socio-cultural trends in the system "personality-family-society" with the values of modern Russian society and the world, while emphasizing the role and importance of the family as part of social life. The radically changed conditions of Russian reality and the ways of family adaptation to the new socio-economic conditions of human life and society are revealed.